Pengelolaan Kelas: Upaya Mengukur Keberhasilan Proses Pembelajaran - Mahmudah Mahmudah (Jurnal Kependidikan, 2018)
Classroom management is an activity or effort to overcome a problem, which is aimed at creating and maintaining a classroom atmosphere that effectively supports the learning program. Effective learning can be done by creating students’ motivation to always be involved and participate in the learning process in the classroom. Creating an effective learning atmosphere can be done through creating a sense of comfort, fun and motivation so as to encourage students to learn. Therefore, success in student learning process must be supported by a competent teacher. The success in improving the effectiveness of the learning process in classroom management needs a teacher who is active (reading a lot) in mastering the material comprehensively, can control the information so as not to be obsolete, has work commitment (sincere, diligent and not easy to complain), and is able to be the model of his/her students.